2005
DOI: 10.1111/j.0305-1870.2005.04250.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic Antihypertensive Effect of Metoprolol in Chronic Aortic Coarctated Rats

Abstract: 1. The aim of the present study was to investigate the possible hypothalamic antihypertensive effect of metoprolol and its action on aminergic neurotransmission in sham-operated (SO) rats and aortic coarctated (ACo) rats at a chronic hypertensive stage using the microdialysis technique. 2. Hypothalamic metoprolol concentrations and their cardiovascular effects were measured after the intravenous administration of 3 mg/kg metoprolol. Based on metoprolol concentrations reached in the anterior hypothalamus, in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…In a previous study, Höcht, Opezzo, and Taira (2005a) evaluated the possible hypothalamic antihypertensive effect of metoprolol and its action on aminergic neurotransmission in sham operated and aortic coarctated hypertensive rats using the reverse microdialysis technique. Intrahypothalamic perfusion with metoprolol induced a significative decrease of blood pressure in coarctated hypertensive animals but not in normotensive rats.…”
Section: Central Nervous Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, Höcht, Opezzo, and Taira (2005a) evaluated the possible hypothalamic antihypertensive effect of metoprolol and its action on aminergic neurotransmission in sham operated and aortic coarctated hypertensive rats using the reverse microdialysis technique. Intrahypothalamic perfusion with metoprolol induced a significative decrease of blood pressure in coarctated hypertensive animals but not in normotensive rats.…”
Section: Central Nervous Systemmentioning
confidence: 99%
“…On the other hand, metoprolol perfusion reduced hypothalamic levels of DOPAC in hypertensive rats but not in sham operated animals. Therefore, the authors concluded that the hypotensive effect of metoprolol perfusion in aortic coartated rats suggest that hypothalamic β-adrenergic blockade is part of the antihypertensive effect of metoprolol in chronic coarctated rats (Höcht et al, 2005a). Local administration of antihypertensive drugs by reverse microdialysis in central nuclei involucred in blood pressure regulation allows elucidating the mechanism of action of this therapeutic class.…”
Section: Central Nervous Systemmentioning
confidence: 99%